The evolution of regional spatial structure influenced by passenger rail service: A case study of the Yangtze River Delta. (28th December 2021) - Liu, Weichen; Guo, Jiaying; Wu, Wei; Cao, Youhui
Abstract: Taking the Yangtze River Delta in China as an example, this paper analyzes the spatial characteristics of passenger rail service in different stages, discusses the evolution of regional multi‐level spatial organization structure under the guidance of passenger rail, and explores the ways to realize efficient and well‐organized regional integration through modern railway infrastructure configuration. Rail transport leads to the formation of several urban subgroups within the Yangtze River Delta. The regional spatial structure is a multi‐level "core‐periphery" nested structure coupled with the internal spatial organization of subgroups and their mutual spatial correlation structure. The organization of intra‐subgroup and inter‐subgroup determine the evolution direction of the whole spatial structure. The development model of constructing a high‐speed railway network with the regional political and economic center cities as hubs has led to each subgroup that starts to rely on these cities to form clusters and achieve spatial reconstruction. In this process, the connection between the "core" areas and the "periphery" areas, as well as among the "periphery" areas within the spatial scope of each level has been strengthened. However, although the gap between the "core" areas and the "periphery" areas has narrowed, it still persists.